Pemanfaatan Telegram dalam Memenuhi Kebutuhan Informasi Akademik Mahasiswa - Ananda, Rizky; Junaidi, Ahmad (Kiwari, 2024)
The Telegram application is effective for use as a general information service as well as special information. Tarumanagara University's Faculty of Communication Sciences uses Telegram as a medium to meet students' academic information needs. The purpose of this research is to measure the use of the Telegram application in meeting the academic information needs of students at the Faculty of Communication Sciences, Tarumanagara University. This research uses an approach with the concept of using social media, which has the dimensions of communication, collaboration, context and connection, as well as the Information Needs Fulfillment Theory, which has the dimensions of personal integrative needs, affective needs, cognitive needs and social integrative needs. Researchers used descriptive quantitative research methods. The results of the research show that the use of Telegram has an influence of 77.6% on fulfilling academic information needs. Aplikasi Telegram efektif digunakan sebagai layanan informasi umum maupun informasi khusus. Fakultas Ilmu Komunikasi Universitas Tarumanagara menggunakan Telegram sebagai media untuk memenuhi kebutuhan informasi akademik bagi mahasiswa. Tujuan dilakukannya penelitian ini adalah untuk mengukur penggunaan aplikasi Telegram dalam memenuhi kebutuhan informasi akademik mahasiswa Fakultas Ilmu Komunikasi Universitas Tarumanagara. Penelitian ini menggunakan pendekatan dengan konsep penggunaan media sosial yang memiliki dimensi communication, collaboration, context, dan connection serta Teori Pemenuhan Kebutuhan Informasi yang memiliki dimensi personal integrative needs, affective needs, cognitive needs, dan social integrative needs. Peneliti menggunakan metode penelitian kuantitatif secara deskriptif. Hasil dari penelitian menunjukkan penggunaan Telegram memiliki pengaruh sebesar 77,6% terhadap pemenuhan kebutuhan informasi akademik sebesar.